Agents related to an operative site infection in operated older adults at the Naval Medical Center, 2013 - 2017 - Hidalgo-Vizarreta, Lucía Fernanda (2019)
Introduction: Surgical site infections (SSI) are part of the most frequent intrahospital infections in the postoperative period of elderly patients. Objective:To determine the agents related to infections of the operative site in the elderly patients after surgery of the Naval Medical Center during January 2013 to December. Methods:An analytical cross sectional study using a secondary data analysis from clinical records of patients older than 65 years post-operated. SSI was studied has outcome, and arterial hypertension, diabetes mellitus, malignant neoplasia, obesity, surgical technique and type of surgery were the agents. Results:Of the 219 older adults, 33.33% (n=73) had SSI. In the bivariate analysis, statistically significant associations were found for diabetes mellitus (PR: 1.49, CI 1.03 - 2.18, p <0.035), type of surgery (PR: 4.63 IC 2.89 -7.42, p <0.05) and surgical technique (PR.0.24, CI 0.13- 0.43, p <0.05). In the multivariate analysis, it was found that emergency type surgery has 4.04 (PR 4.04, IC 2.55 - 6.40, p <0.05) times chance for SSI compared to the programmed surgery, and the laparoscopic technique surgery has 0.29 (PR 0.29, CI 0.17-0.52, p <0.05) chance of SSI compared to the open technique. Conclusion: Laparoscopic operative technique decreases the likelihood of ISO, and emergency surgery increases its likelihood in elderly patients.